EXPLORING THE HISTORICAL CONTEXT AND FUTURE PROSPECTS OF PAK CHINA RELATIONS - Anwar ul Mustafa Shah; Zunera Memon; Dr.Farhana Kousar (Journal of Religion and Society, 2024)
The relationship between Pakistan and China is one of the most strategically significant and historically rich bilateral partnerships in contemporary geopolitics. This study examines the evolution of Pak-China relations, tracing their origins to the early years following Pakistan's independence in 1947 and the establishment of formal diplomatic ties in 1951. It highlights key milestones, including the 1963 border agreement, China's assistance in Pakistan’s nuclear program, and the mutual collaboration during the Cold War era. The research further underscores the role of economic cooperation, such as the development of the China-Pakistan Economic Corridor (CPEC), which has become a cornerstone of their partnership under China's Belt and Road Initiative (BRI). The article delves into the multi-faceted nature of this alliance, which spans defense, trade, technology, and cultural exchanges. It explores how shared strategic interests, such as counterbalancing regional rivalries and promoting economic connectivity, have shaped their enduring bond. Furthermore, the study analyzes the challenges and criticisms faced by this partnership, including concerns about Pakistan's growing economic dependence on China, regional tensions with India, and the evolving dynamics of international relations. Looking ahead, the article assesses the prospects for Pak-China relations in light of emerging global trends. It discusses opportunities to deepen cooperation in renewable energy, digital technology, and regional stability initiatives, while addressing potential obstacles like debt management and external geopolitical pressures. The study emphasizes the need for both nations to ensure mutual benefits and sustainable growth, preserving the long-term integrity of their alliance. This comprehensive analysis provides valuable insights into the historical, economic, and geopolitical dimensions of Pak-China relations. It concludes that the partnership remains a pivotal factor in the regional and global landscape, with promising prospects for continued collaboration in the face of evolving challenges and opportunities. Keywords: Pakistan-China Relations, CPEC, Belt and Road Initiative, Regional Geopolitics, Economic Cooperation, Strategic Partnership, Historical Context, Future Prospects.